2022
DOI: 10.1080/09537287.2022.2106446
|View full text |Cite
|
Sign up to set email alerts
|

Workforce resilience in the post-COVID-19 era: differences based on manufacturing–service orientation and firm size

Abstract: The devastating impact of COVID-19 on businesses has led to the redefinition of workforce resilience. This study hence explores workforce resilience factors that will be important in the post-COVID-19 era. It investigates whether these factors perform differently in the manufacturing vs. the service sector and in small and medium enterprises (SMEs) vs. large firms. Sixty-five firms were studied in Malaysia and analysed through Rasch modelling. The results indicate that three workforce resilience factors (posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…They are decision-making and work-life balance. Findings will help managers to design strategies to leverage workforce resilience in post covid era (Soomro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They are decision-making and work-life balance. Findings will help managers to design strategies to leverage workforce resilience in post covid era (Soomro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Markman and Venzin (2014) have found that smaller banks are more resilient than larger ones. Organizational managers can take different measures to address post-COVID resilience for different firm sizes (Soomro et al. , 2022).…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Markman and Venzin (2014) have found that smaller banks are more resilient than larger ones. Organizational managers can take different measures to address post-COVID resilience for different firm sizes (Soomro et al, 2022). Therefore, this study includes firm size to explore the impact of CSR on organizational resilience for firms of different sizes.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested rethinking agile retailing, identifying a new role for retailers t o w a r d s s o c i e t y, e n c o u r a g i n g d i g i t a l communication, and keeping the interests of the consumers as the core of their business. Soomro et al (2022) explored that control of emotions, a sense of responsibility, and positive thoughts are hard to combat in manufacturing. For small and medium enterprises (SMEs), dealing with innovation, a sense of responsibility, cognitive processes, involvement and differentiation, and positive thoughts can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Arora and Pratibha (2021) investigated how workers in an IT company felt about the HRM procedures. The current literature identifies the unique challenges faced by HRM professionals (Anjum et al, 2022), how the challenges can impact the strength of workers (Soomro et al, 2022), and various intervention types to combat the obstacles (Pantano et al, 2020). Researchers explored the confidence levels of different professionals to deal with the challenges (Ricou et al, 2021) and the impact of the leadership style adopted by managers and owners towards employees to deal with the challenges (Alsharif et al, 2021).…”
Section: Introductionmentioning
confidence: 99%